2017
DOI: 10.1371/journal.pone.0177861
|View full text |Cite
|
Sign up to set email alerts
|

An androgen response element driven reporter assay for the detection of androgen receptor activity in prostate cells

Abstract: The androgen receptor (AR) transcription factor plays a key role in the development and progression of prostate cancer, as is evident from the efficacy of androgen-deprivation therapy, AR is also the most frequently mutated gene, in castration resistant prostate cancer (CRPC). AR has therefore become an even more attractive therapeutic target in aggressive and disseminated prostate cancer. To investigate mechanisms of AR and AR target gene activation in different subpopulations of prostate cancer cells, a tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…To address this question, we used an AR-responsive reporter construct in which a sequence of six copies of the androgen-response element (ARE) had been cloned in front of the luciferase gene 38 . We first confirmed that treatment with dihydrotestosterone (DHT) resulted in a robust activation of this reporter construct in LNCaP and C4-2 cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To address this question, we used an AR-responsive reporter construct in which a sequence of six copies of the androgen-response element (ARE) had been cloned in front of the luciferase gene 38 . We first confirmed that treatment with dihydrotestosterone (DHT) resulted in a robust activation of this reporter construct in LNCaP and C4-2 cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indirect immunofluorescence assays were performed as previously described (19). The primary antibody used was anti-β-catenin (Cat.…”
Section: Indirect Immunofluorescence Assaymentioning
confidence: 99%
“…AR-V7 transcriptional activity has been shown to depend on the D-box domain shown to mediate AR-V7 homodimerization in the nucleus (Centenera et al, 2008; Xu et al, 2015). To determine the potential impact of D-box domain on AR-V7 nuclear import which is a pre-requisite for its transcriptional activity, we generated a construct encoding GFP-AR-V7 containing two established, functionally-inactivating D-box mutations (A596T, S597T) and transiently transfected PC3 cells stably expressing the ARE-mCherry reporter in order to measure ARE activity in single cells (Azeem et al, 2017). Cells transfected with GFP-AR-V7 alone had an average of 71% nuclear AR-V7 with concomitant mCherry expression indicating ARE-transactivation.…”
Section: Resultsmentioning
confidence: 99%